Changes in the molecular profiles of large-vessel vasculitis treated with biological disease-modifying anti-rheumatic drugs and Janus kinase inhibitors - Matsumoto, Kotaro; Suzuki, Katsuya; Takeshita, Masaru; Takeuchi, Tsutomu; Kaneko, Yuko (Frontiers in immunology, 2023)
Giant cell arteritis and Takayasu arteritis are two types of primary large-vessel vasculitis (LVV). Although glucocorticoids (GC) are the standard treatment for LVV, the disease relapse rates are high. Recent clinical trials on biological disease-modifying anti-rheumatic drugs (bDMARDs) and Janus kinase (JAK) inhibitors have demonstrated their efficacy in reducing LVV relapse rates and GC dosages. However, the control of residual inflammation and degenerative alterations in the vessel wall remains an outstanding requirement in the clinical management of LVV. The analysis of immune cell phenotypes in patients with LVV may predict their response to treatment with bDMARDs and JAK inhibitors and guide their optimal use. In this mini-review, we focused on molecular markers, including the immune cell proportions and gene expression, in patients with LVV and in mouse models of LVV treated with bDMARDs and JAK inhibitors.